Radiation-induced gliomas represent H3-/IDH-wild type pediatric gliomas with recurrent PDGFRA amplification and loss of CDKN2A/B - Deng, Maximilian; Sturm, Dominik; Pfaff, Elke; Sill, Martin; Stichel, Damian; Balasubramanian, Gnana Prakash; Tippelt, Stephan; Kramm, Christof; Donson, Andrew M.; Green, Adam L.; Jones, Chris; Schittenhelm, Jens; et al. (Nature Communications, 2021)
Long-term complications such as radiation-induced second malignancies occur in a subset of patients following radiation-therapy, particularly relevant in pediatric patients due to the long follow-up period in case of survival. Radiation-induced gliomas (RIGs) have been reported in patients after treatment with cranial irradiation for various primary malignancies such as acute lymphoblastic leukemia (ALL) and medulloblastoma (MB). We perform comprehensive (epi-) genetic and expression profiling of RIGs arising after cranial irradiation for MB (n = 23) and ALL (n = 9). Our study reveals a unifying molecular signature for the majority of RIGs, with recurrent PDGFRA amplification and loss of CDKN2A/B and an absence of somatic hotspot mutations in genes encoding histone 3 variants or IDH1/2, uncovering diagnostic markers and potentially actionable targets.
Published 20 September 2021
Gesehen am 23.03.2022